Association of Mycobacterium tuberculosis genotypes and treatment outcome in pulmonary tuberculosis patients in Tshwane Metropolitan area - Lekalakala, M. Ruth (University of Pretoria, 2016)
Dissertation (MSc)--University of Pretoria, 2015.